2006
DOI: 10.1007/s10038-006-0090-5
|View full text |Cite
|
Sign up to set email alerts
|

Combinational effect of genes for the renin–angiotensin system in conferring susceptibility to diabetic nephropathy

Abstract: To elucidate the role of the renin-angiotensin system (RAS) in diabetic nephropathy, we examined the association between diabetic nephropathy in a large cohort of Japanese type 2 diabetic patients and polymorphisms within the genes that encode angiotensin-converting enzyme (ACE), angiotensinogen (AGT) and angiotensin II receptor type 1 (AGTR1). Single nucleotide polymorphisms (SNPs) within these genes were genotyped using invader assay in 747 nephropathy cases and 557 control subjects. Eight SNPs within the AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 25 publications
1
23
1
Order By: Relevance
“…Along the same line, Bantis et al, described a synergistic association of AGT M235T and ACE I/D polymorphisms also with the progression of IgA nephropathy to ESKD (85) and found that those patients who carried more than two ACE-D or AGT-T alleles (that is the DD/TT, DD/MT, or ID/TT genotypes) were the ones with the largest benefit from ACE inhibitor therapy. In contrast with the above findings, however, Osawa et al (86) failed to detect any significant association of AT1R A1166C, ACE I/D, and AGT M235T polymorphisms with diabetic renal disease. Thus, whether and to what extent the interactions between AGT, and AT1R, and ACE polymorphisms may affect the progression of diabetic and nondiabetic chronic renal disease and response to RAS inhibitor therapy is still unclear.…”
Section: Other Ras Polymorphisms and Their Interactions With The Ace contrasting
confidence: 57%
“…Along the same line, Bantis et al, described a synergistic association of AGT M235T and ACE I/D polymorphisms also with the progression of IgA nephropathy to ESKD (85) and found that those patients who carried more than two ACE-D or AGT-T alleles (that is the DD/TT, DD/MT, or ID/TT genotypes) were the ones with the largest benefit from ACE inhibitor therapy. In contrast with the above findings, however, Osawa et al (86) failed to detect any significant association of AT1R A1166C, ACE I/D, and AGT M235T polymorphisms with diabetic renal disease. Thus, whether and to what extent the interactions between AGT, and AT1R, and ACE polymorphisms may affect the progression of diabetic and nondiabetic chronic renal disease and response to RAS inhibitor therapy is still unclear.…”
Section: Other Ras Polymorphisms and Their Interactions With The Ace contrasting
confidence: 57%
“…Bantis et al (49) reported an association between concomitant presence of ACE I/D and AGT M235T variants on the progression of IgG nephropathy to ESRD and better response to ACE inhibitor therapy in the presence of these variants. However, Subsequent report of Osawa et al (50) failed to indicate any significant interaction between ACE I/D, AGT M235T and AT1R A1166C variants on the risk of DN.…”
Section: Interaction Between Ace I/d and Variants Of Ras Genesmentioning
confidence: 93%
“…The role of two genes variants of angiotensinogen (AGT) and angiotensin II type-1 receptor (AT1R) and their interaction with ACE I/D polymorphism on the susceptibility to DN has been investigated with controversy (47)(48)(49)(50).…”
Section: Interaction Between Ace I/d and Variants Of Ras Genesmentioning
confidence: 99%
“…tensinogen, and the AT 1 receptor may be associated with complex multigenic diseases (41). The genetic variations inside the RAS that may affect the function of its components might have an influence on genetic predisposition to diabetes and renal and cardiovascular diseases (8,9,40,46). A better understanding of the relationship between the ability to increase vessel density in response to physiological electrical stimuli in adult skeletal muscle and the regulation of renin, a key enzyme in the production of ANG II, may bring new insights to the treatment of several diseases, since microvascular rarefaction and arteriolar remodeling are both necessary physiological adaptations that can become maladaptive and lead to target organ damage.…”
Section: Renin Gene Expression and Skeletal Muscle Angiogenesismentioning
confidence: 99%